The Cumulative Role of Impoundments in Streamflow Alteration. (20th December 2021) - Brogan, Connor; Burgholzer, Robert; Keys, Tyler; Kleiner, Joseph; Shortridge, Julie; Scott, Durelle
Abstract: Small impoundments are numerous throughout river corridors. Limited data on their size and outflow have made it difficult to assess how these smaller impoundments cumulatively impact streamflow. This study combined rainfall‐runoff data from the Chesapeake Bay Watershed Model with a routing framework to develop a hydrologic model capable of analyzing flow alteration induced by cumulative impoundment. Using standard design processes and satellite imagery, simulations of impoundment hydraulics were assembled for both small and large impoundments. Eleven of the 170 impoundments in the Difficult Run watershed were modeled to assess their cumulative impact on downstream flow from 1984 to 2005. Multiple simulations were analyzed to determine incremental effects. We found that flow alteration increased with impoundment density. Impoundments prolonged storm hydrographs, increasing median and baseflows, and decreasing peak streamflow downstream. Impoundment size and location impacted downstream flow alteration as headwater channels ran dry and evaporation from impoundments with high surface area to storage ratios decreased extreme low flows. Large reservoirs had a greater impact on median flows, as small ponds dominated low flow alteration. Including a greater fraction of the watershed's 170 small impoundments may further increase flow alteration. These results suggest that small impoundments play a large role in determining water availability, particularly during droughts.